2008
DOI: 10.1086/592509
|View full text |Cite
|
Sign up to set email alerts
|

A Simplified and Standardized Polymerase Chain Reaction Format for the Diagnosis of Leishmaniasis

Abstract: The Leishmania OligoC-TesT showed high specificity and sensitivity in clinical samples and was able to detect the parasite in samples obtained by less invasive means, such as blood, lymph, and lesion scrapings. The assay is a promising new tool for simplified and standardized molecular detection of Leishmania parasites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
71
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(75 citation statements)
references
References 34 publications
2
71
0
2
Order By: Relevance
“…Furthermore, there is a lack of standardization in the selection of target Leishmania DNA sequences and experimental PCR protocols used in laboratories worldwide, which complicates objective comparisons of test sensitivity and specificity. In order to address some of these issues, a commercially available PCR test kit (Leishmania OligoC-TesT) has been developed and validated for detection of Leishmania parasite DNA in human specimens (3,6). Sensitivities of the test ranged from 77.8% to 100% for clinical samples from patients with visceral leishmaniasis in Sudan and Kenya, with a limit of detection of 1 parasite in 180 l blood (3).…”
mentioning
confidence: 99%
“…Furthermore, there is a lack of standardization in the selection of target Leishmania DNA sequences and experimental PCR protocols used in laboratories worldwide, which complicates objective comparisons of test sensitivity and specificity. In order to address some of these issues, a commercially available PCR test kit (Leishmania OligoC-TesT) has been developed and validated for detection of Leishmania parasite DNA in human specimens (3,6). Sensitivities of the test ranged from 77.8% to 100% for clinical samples from patients with visceral leishmaniasis in Sudan and Kenya, with a limit of detection of 1 parasite in 180 l blood (3).…”
mentioning
confidence: 99%
“…Recently, the Leishmania OligoC-TesT was introduced as an innovative PCR format for simplified and standardized molecular diagnosis of Leishmania infections (7). We have demonstrated that the Leishmania OligoC-TesT offers performance comparable to that of conventional kDNA PCR for lesion scrapings in cases of suspected and confirmed CL in Peru.…”
Section: Discussionmentioning
confidence: 98%
“…The Leishmania OligoC-TesT was performed as described by Deborggraeve et al (7). Briefly, Leishmania DNA was amplified by PCR and mixed with an equal volume of migration buffer preheated at 55°C.…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…The implementation of more simple assays such as PCR-oligochromatography might constitute a promising alternative in the future. 65 Serologic diagnosis is not used in CL diagnosis in Bolivia. Sensitivity and specificity of tests can be variable, with tests suffering from cross-reaction with Trypanosoma cruzi , which is sympatric in many leishmaniases-endemic areas.…”
Section: Disease Distribution Notification and Incidencementioning
confidence: 99%